SMFA Senior Thesis Project May, 2017. - Sageman, Christopher. (Tufts Archival Research Center, 2017)
This body of work exposes the hypocrisy of contemporary American culture. Using density as a visual and artistic strategy, the work reveals a narrative of what it means to be an American. With contemporary American culture reaching a point of critical mass, whether it besocial media, television, or advertising, the average American is under the constantbombardment of images and text, news and propaganda. Through drawing, painting, andappropriated images and text, the work looks critically at the irony of the present climate in America. Employing American iconography of the past as well as the present, and removing textand images from their original context in magazines, advertisements, trash, etc. with theintention of creating an alternative narrative, which problematizes the American value system. The notion of what the American dream is becomes abstracted and viewed through a critical lens.; Keywords: American history, iconography, draw, paint, installation, density, satire, satan, 666.